Transductive support vector machines for cross-lingual sentiment classification. - Nguyen, Thi Thuy Linh (ĐHCN, 2017)
Sentiment classification has been much attention and has many useful applications on business and intelligence. This thesis investigates sentiment classification problem employing machine learning technique.